2014
DOI: 10.1177/1352458514531084
|View full text |Cite
|
Sign up to set email alerts
|

Identical lesion morphology in primary progressive and relapsing–remitting MS –an ultrahigh field MRI study

Abstract: Potential differences between primary progressive (PP) and relapsing-remitting (RR) multiple sclerosis (MS) have been controversially discussed. In this study, we compared lesion morphology and distribution in patients with PPMS and RRMS (nine in each group) using 7 T MRI. We found that gray and white matter lesions in PPMS and RRMS patients did not differ in their respective morphological characteristics (e.g., perivascular p = 0.863, hypointense rim p = 0.796, cortical lesion count p = 0.436). Although limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
7
30
0
1
Order By: Relevance
“…The proportion of total lesions with a central vein was not related to the clinical phenotype -a finding that was also supported by another study 32 . However, when lesions were classified according to their location, the authors reported that central veins were most prevalent in periventricular lesions (94%).…”
Section: The Central Vein In Ms Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The proportion of total lesions with a central vein was not related to the clinical phenotype -a finding that was also supported by another study 32 . However, when lesions were classified according to their location, the authors reported that central veins were most prevalent in periventricular lesions (94%).…”
Section: The Central Vein In Ms Discussionsupporting
confidence: 70%
“…This first in vivo demonstration of the perivenous distribution of MS plaques was further confirmed in 2008 using ultra-high-field MRI 29,30 . Follow-up imaging studies confirmed this finding in relapsing-remitting MS (RRMS), secondary progressive MS (SPMS) and primary progressive MS (PPMS) 31,32 . This perivenous distribution in different MS subtypes is illustrated in FIG.…”
Section: The Central Vein In Ms Discussionmentioning
confidence: 65%
“…Lesion morphology (iron deposition, the presence of the central vein), lesion count, and the proportion of cortical-to-total lesion counts were similar in PPMS and RRMS groups. 27 In PPMS, more diffuse abnormalities in the brain and spinal cord along with smaller caudate volume were apparent compared with RRMS. 28 In PPMS, clinicoradiologic correlation was weak for cerebral T1LL/ T2LL but was stronger between spinal cord symptoms and spinal cord MR imaging parameters.…”
Section: Discussionmentioning
confidence: 93%
“…There is ongoing debate as to whether or not primary progressive (PP) and secondary progressive (SP) multiple sclerosis (MS) are essentially the same disease, barring the preceding relapsing-remitting (RR) phase: the age at onset and rate of progression are similar 1 and lesion morphology in relapse-onset and PPMS are identical, 2 but differences have been observed in both MRI and histopathological studies. 3,4 Post-mortem studies have recently revealed meningeal inflammation in all types of MS, [5][6][7] although the most structured form -lymphoid follicle-like aggregates -have only been observed in SPMS, not in PPMS.…”
Section: Introductionmentioning
confidence: 99%